Sistem Informasi Pendataan Masyarakat Tidak Mampu Berbasis Website Pada Kelurahan Binanga, Kecamatan Mamuju, Kabupaten Mamuju - B, Syaifuddin; Syaharuddin, Syaharuddin (Jurnal Ilmiah Multidisiplin Amsir, 2024)
The design of a website-based application for the Information System for Data Collection on Disadvantaged Communities in Binanga Mamuju Subdistrict, among other things, is to simplify the process of data collection on underprivileged communities in Binanga subdistrict, which was previously done manually so it was inefficient. The impact is that many files or documents are lost due to the absence of a system that manages this data. The aim of this research is to build an application system that can be accessed from anywhere using an internet connection so that data collection on people who cannot afford it can be done or accessed online. The research location is located at the Binanga Mamuju subdistrict office. The method used in research design is the Watervall method. This application system design was built using the Visual Studio Code application as a code editor with the PHP programming language and MySQL as the database. The results of the research are in accordance with the initial design where the application for data collection on disadvantaged communities in the Mamuju sub-district has run according to the initial design. The conclusion of this research is that the resulting application is able to operate well and is able to streamline the tasks of sub-district employees in the input process and the data is stored properly in the system database.